Ownership of the land in the context of the special legal regime of the lands belonging to the Nature Reserve Fund and ways of their protection - Малярчук, Назар Вікторович; Овчинников, Денис Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article considers problems of using and disposing of the land resources according to the legislation of Ukraine. In addition, the authors examine the legal regime of the lands belonging to the Nature Reserve Fundand ways of their protection.